Investigating Reaction Mechanisms in Typical Acid-Base Systems Using pH Metric Titration - Mallick, Abhijit (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
pH-metric study is very useful to measure the acidity or alkalinity of different types of solutions. In acid-base titrations, also pH meter is also used to find out the neutralization volume. pH-metric study is also useful in determining water quality, as documented by several scientists. In general, the nature of chemical reactions is studied by separating the products, followed by analyzing the products using different methods like spectroscopic methods, chromatographic methods, etc. The objective of the present study is to investigate the nature of chemical reactions using pH - meter. Two types of reactions are studied: (a) neutralization of a Na2CO3 solution by HCl solution and (b) neutralization of NaOH solution by oxalic acid solution. In both cases, one component is acid and the other component is base. So, a salt is produced as the main product, but the nature of the reaction, i.e., whether the reaction occurs in a single step or multiple steps, cannot be identified by any standard methods. In the present study, the aforementioned reactions are closely monitored using pH - meter. In case of neutralization of Na2CO3 by HCl two sharp drops in pH are observed, one at pH = 9 and another at pH = 5.7. The observation clearly indicates that the neutralization reaction of a given Na2CO3 solution by HCl the solution occurs in two steps. It is believed that initially, the carbonate ion is converted to bicarbonate ion in alkaline pH range and later on in acid pH range bicarbonate ion is converted to carbonic acid. In case of neutralization of a given NaOH solution by oxalic acid solution, only one sharp drop in pH is observed at pH = 10.2, indicating that the reaction is believed to occur in a single step. On the basis of experimental studies, the probable steps of each reaction are proposed to explain the above neutralization reactions. Besides the conventional spectroscopic method, this novel method is believed to be useful to monitor other chemical reactions accurately, exploring future research works. This pH - metric study is expected to have potential in the development of analytical chemistry and chemical processes related to industry.